Self-harm Risk Among Adolescents and the Phenomenon of the “Blue Whale Challenge”: Case Series and Review of the Literature - LUPARIELLO, FRANCESCO; Curti Serena; Coopo Elena; RACALBUTO, Sara; Di Vella Giancarlo (Journal of Forensic Sciences, 2019)
The “Blue Whale Challenge” is a dangerous internet phenomenon. As per media reports, it involves a series of life-threatening tasks imposed by a “curator” to “players,” who must fulfill the whole list, and it ends with the suicide of the player. The authors report the data of five suspected cases of “Blue Whales” managed from January 2016 to December 2017 by the staff of a unit (the “Bambi Unit” of the Pediatric Hospital “Regina Margherita” of Turin, Italy) that is dedicated to the evaluation of suspected abused children. Then, they analyzed this data in the light of the literature regarding self-harm. This comparison highlights the role of the internet in the spreading of self-harm behavior among vulnerable adolescents who are characterized by epidemiological, psychological, psychiatric, social, and cultural risk factors. In conclusion, the authors suggest a multidisciplinary and specialized approach in the evaluation of adolescents who committed self-harm activities.